Pengaruh Location Store, Testimoni dan Tagline Terhadap Penjualan Produk UMKM (Studi Kasus DJ Dimsum Pematangsiantar) - Fachri Husaini; Tri Indah Fadhila Rahma; Reni Ria Armayani Hasibuan (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
This study aims to determine the effect of store location, testimonials and taglines on product sales at DJ Dimsum Pematangsiantar. This type of research uses quantitative research methods. Data collection was carried out by distributing questionnaires to consumers of DJ Dimsum Pematangsiantar. The sampling technique in this study was the nonprobability sampling technique, the accidental sampling technique, and the number of samples used was 85 respondents. The validity test used in this study was to use the corrected item-total correlation, the reliability test in this study used Cronbach's alpha and the analysis technique used was veranda linear regression. The results of this study indicate that 1) Store Location, Testimonial and Tagline simultaneously have a positive effect on MSME product sales at DJ Dimsum Pematangsiantar which can be explained by the Location Store, Testimonial and Tagline variables. While the rest is explained by other variables not explained in this study. 2) Location Store has a positive effect on product sales, so that if the location selection is good and right, sales of MSME products at DJ Dimsum Pematangsiantar will increase. 3) Testimonials have a positive and significant effect on product sales, so that if the testimonials given by consumers get better, it will increase sales of MSME products at DJ Dimsum Pematangsiantar. 4) The tagline has a positive and significant effect on product sales, so that if the tagline is used properly, it will increase sales of MSME products at DJ Dimsum Pematangsiantar.